Martin Luther King, Jr. : A Man of Peace - Garnet N Jackson; Karen Foster (United States Scholastic, 2001)
Offers biographical information on the Civil Rights leader whose non-violent protests helped to ease racial discrimination in America.
Keywords: Peace Justice and Strong Institutions; Biographies-Autobiographies-Junior Fiction -- Biographies-Autobiographies-Junior Fiction